Fenomena self diagnose dan glorifikasi gangguan mental pada platfrom media sosial - Husna, Faidatul (Maliki Interdisciplinary Journal, 2024)
As much as 167 of Indonesia’s population this year has been categorized as active social media users. In its use, social media quickly provides various types of information, one of them is about mental health issues. The amount of information on mental health issues certainly has a good impact on individuals, especially in being aware of mental disorders. However, the disclosure of information on social media has increasingly leads to an increase of self-diagnosis in individuals, without the initiative to validate it with professionals. Disclosure of information on social media has also led to the glorification of mental disorders. This research aims to thoroughly explore the phenomenon that is still being discussed on social media platforms, self-diagnosis and glorification of mental disorders, definitions, and the prevention.